2019
DOI: 10.1080/17453054.2018.1548267
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey research investigating how medical students use clinical photographs to support their learning

Abstract: T England. The design used was cross-sectional survey research. The data collection method was a self-completion online survey. A total of 283 students participated in the study. The proportion of students using clinical photographs was 87%, p= 0.217. The medical subject discipline in which clinical photographs were considered by students as most useful were dermatology ( T V Qlibrary made available through their medical school was 92%. The main barrier to using existing photographic resources was awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This is also a service that some MIDs are already able to provide. But as seen in other studies (Dakin & Coates, 2019), our data demonstrate that awareness of the role and function of MIDs amongst users remains a key barrier to use. Over 60% of medical students had no or limited understanding of the role of MIDsand without awareness, users can neither consider nor use the valuable services that MIDs provide.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is also a service that some MIDs are already able to provide. But as seen in other studies (Dakin & Coates, 2019), our data demonstrate that awareness of the role and function of MIDs amongst users remains a key barrier to use. Over 60% of medical students had no or limited understanding of the role of MIDsand without awareness, users can neither consider nor use the valuable services that MIDs provide.…”
Section: Discussionsupporting
confidence: 81%
“…Their conclusions were that while the high quality of medical photographs makes them an attractive resource for education, the high cost of internet-based commercial archives, storage capacity and patient consent remained significant barriers to access. Indeed, the only direct exploration into the topic of our research to date is Dakin and Coates (2019), who investigated the use of medical photographs by medical students in a cross-sectional quantitative survey. Their key findings were that student awareness was the main barrier to using existing medical illustration archives.…”
Section: Introductionmentioning
confidence: 99%
“…52 A recent survey demonstrated that 87% of medical students use clinical images. 53 The Internet was the primary source (96%), and approximately one-third of medical students found it difficult to find appropriate images. The cost, validity, consent level, file size, and copyright status were important factors affecting students' choice for using clinical images.…”
Section: Discussionmentioning
confidence: 99%
“…The cost, validity, consent level, file size, and copyright status were important factors affecting students' choice for using clinical images. 53 Medical educators sourced medical images mainly from open-access search engines, social media, and student textbooks. Nevertheless, they were worried about copyright violation and consent level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation